A quick and selected overview of the expert panel on effective ways of investing in health - Pedro Pita Barros (BMC, 2017)
Abstract The European Commission created the Expert Panel on Effective Ways of Investing in Health (EXPH) in 2012. The EXPH started its activities in July 2013 and ended its first term in May 2016. A personal review of the Expert Panel contributions in its first term is provided.